A new species of isopod (Isopoda: Flabellifera: Sphaeromatidae) from Cuba, with an identification key for the species of Paraimene - Manuel Ortiz Touzet (Revista Mexicana de Biodiversidad)
A new species of isopod crustacean belonging to the genus Paraimene (Isopoda, Flabellifera, Sphaeromatidae) is described. The new species was collected from Cojimar Bay, La Habana Province, Cuba. The differences among Paraimene danieli new species and other known species of the genus Paraimene are given. Finally, a identification key for all Paraimene species is also provided.